2021
DOI: 10.4049/jimmunol.2001082
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional Tier 2–Neutralizing Antibodies Cloned following HIV-1 Env Macaque Immunization Mirror Native Antibodies in a Human Donor

Abstract: Vaccine efforts to combat HIV are challenged by the global diversity of viral strains and shielding of neutralization epitopes on the viral envelope glycoprotein trimer. Even so, the isolation of broadly neutralizing Abs from infected individuals suggests the potential for eliciting protective Abs through vaccination. This study reports a panel of 58 mAbs cloned from a rhesus macaque (Macaca mulatta) immunized with envelope glycoprotein immunogens curated from an HIV-1 clade C–infected volunteer. Twenty mAbs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…Our study provides evidence that the nAb outcomes we observed were imprinted on the Z1800M and R66M T/F Envs to some extent, a concept that has been supported by other studies in RM and in HIV transmission pairs [6,[59][60][61]. Our approach also highlights the complexity of generating soluble HIV trimers in the context of diverse variants.…”
Section: Convergence Of Neutralizing Antibody Targeting In Hiv-1 Infe...supporting
confidence: 83%
“…Our study provides evidence that the nAb outcomes we observed were imprinted on the Z1800M and R66M T/F Envs to some extent, a concept that has been supported by other studies in RM and in HIV transmission pairs [6,[59][60][61]. Our approach also highlights the complexity of generating soluble HIV trimers in the context of diverse variants.…”
Section: Convergence Of Neutralizing Antibody Targeting In Hiv-1 Infe...supporting
confidence: 83%
“…The use of computational inference methods, such as IgDiscover (6), partis (17) and TIgGER (18), provides a means to define VDJ genotypes in individuals in a more time-efficient manner (6,17,18). This approach has been used successfully for studies of antibody diversity, affinity maturation and B cell lineage tracing in immunized macaques (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The VC10014 immunogen platform has consistently demonstrated the induction of Tier 2 heterologous NAbs ( 20 , 21 , 39 ). Although modest, the Imm group showed a trend toward enhanced protection from repeated heterologous challenge, as well as conferring decreased viral burden upon infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we utilized the VC10014 DNA-protein co-immunization vaccine platform consisting of gp160 plasmids and trimeric gp140 proteins derived from a clade B HIV-1 infected subject who developed broadly neutralizing plasma Abs, which previously induced Tier 2 heterologous neutralizing Abs in rabbits and rhesus macaques ( 19 21 ). We evaluated the influence of CD4+ T cell depletion during the vaccination regimen on the characteristics of the Env-specific humoral response in rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%